ANALYSIS OF THE EFFECT OF FINANCING, THIRD PARTY FUNDS (DPK) AND FINANCING TO DEPOSIT RATIO (FDR) ON TOTAL ASSETS OF SHARI'AH COMMERCIAL BANKS - Al, Alfian Muhammad; Ula, Tajul Ula; Salwa, Salwa Fachri Assa’dy (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2022)
ANALYSIS OF THE EFFECT OF FINANCING, THIRD PARTY FUNDS (DPK) AND FINANCING TO DEPOSIT RATIO (FDR) ON TOTAL ASSETS OF SHARI'AH COMMERCIAL BANKS Abstract Purpose: This study aims to analyze the impact of financing, third-party funds (DPK), and Financing to Deposit Ratio (FDR) on the total assets of Shari'a Commercial Banks in Aceh province. Design/methodology/approach: The research adopts a quantitative approach employing a time-series data analysis model with the Ordinary Least Square (OLS) model. Findings: The results reveal a positive influence of financing and third-party funds (DPK) on the total assets of Shari'a Commercial Banks in Aceh province. Research limitations/implications: Despite the positive effects observed, potential limitations may include external economic factors that could impact the findings. Future research could explore additional variables for a more comprehensive analysis. Practical implications: The study recommends that Shari'a Commercial Banks in Aceh enhance their Shari'a banking products, particularly in the form of financing and third-party funds (DPK), to maximize total assets and positively impact the welfare and health of Shari'a Commercial Banks Keywords: Third-Party Funds (DPK), Financing to Deposit Ratio (FDR), Total Assets, OLS Data Time Series Model. ANALISIS PENGARUH PEMBIAYAAN, DANA PIHAK KETIGA (DPK) DAN FINANCING TO DEPOSIT RATIO (FDR) TERHADAP TOTAL ASET BANK UMUM SYARIAH Abstrak Tujuan: Penelitian ini bertujuan untuk menganalisis pengaruh pembiayaan, dana pihak ketiga (DPK), dan Financing to Deposit Ratio (FDR) terhadap total aset Bank Umum Syariah di Provinsi Aceh. Desain / metodologi / pendekatan: Penelitian ini mengadopsi pendekatan kuantitatif menggunakan model analisis data time-series dengan model Ordinary Least Square (OLS). Kesimpulan: Hasil penelitian menunjukkan pengaruh positif pembiayaan dan dana pihak ketiga (DPK) terhadap total aset Bank Umum Syariah di provinsi Aceh. Keterbatasan / implikasi penelitian: Terlepas dari efek positif yang diamati, keterbatasan potensial dapat mencakup faktor ekonomi eksternal yang dapat memengaruhi temuan. Penelitian di masa depan dapat mengeksplorasi variabel tambahan untuk analisis yang lebih komprehensif. Implikasi praktis: Studi ini merekomendasikan agar Bank Umum Syariah di Aceh meningkatkan produk perbankan Syariah mereka, khususnya dalam bentuk pembiayaan dan dana pihak ketiga (DPK), untuk memaksimalkan total aset dan berdampak positif bagi kesejahteraan dan kesehatan Bank Umum Syariah Kata kunci: Dana Pihak Ketiga (DPK), Financing to Deposit Ratio (FDR), Total Aset, Model Time Series Data OLS.